2008
DOI: 10.1007/s10526-008-9181-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of Radopholus similis in banana by combined application of the mutualistic endophyte Fusarium oxysporum strain 162, the egg pathogen Paecilomyces lilacinus strain 251 and the antagonistic bacteria Bacillus firmus

Abstract: The biological control efficacy of single or multiple applications of the mutualistic endophyte Fusarium oxysporum strain 162, the egg pathogen Paecilomyces lilacinus strain 251 and the antagonistic bacteria Bacillus firmus toward Radopholus similis was investigated in pot trials with banana under glasshouse conditions. R. similis was controlled substantially in single and combined applications of F. oxysporum with P. lilacinus or B. firmus. The combination of F. oxysporum and P. lilacinus caused a 68.5% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Some studies have shown that the endophyte F. oxysporum has the ability to induce a systemic resistance in banana plants against R. similis , reducing the penetration and the population density of this nematode (Felde et al., ; Paparu, Dubois, Coyne, & Vijoen, ; Vu, Hauschild, & Sikora, ). Other studies evidenced that the endophyte may exert an antagonistic activity against R. similis , which makes it a promising biological control agent (Athman et al., ; Mendoza & Sikora, ). Thus, it is believed that some F. oxysporum isolates in this study might have reduced the burrowing nematode population density either by biological control effects or by inducing plant resistance to the nematode, which may explain the low frequencies and low population densities found in the studied areas (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that the endophyte F. oxysporum has the ability to induce a systemic resistance in banana plants against R. similis , reducing the penetration and the population density of this nematode (Felde et al., ; Paparu, Dubois, Coyne, & Vijoen, ; Vu, Hauschild, & Sikora, ). Other studies evidenced that the endophyte may exert an antagonistic activity against R. similis , which makes it a promising biological control agent (Athman et al., ; Mendoza & Sikora, ). Thus, it is believed that some F. oxysporum isolates in this study might have reduced the burrowing nematode population density either by biological control effects or by inducing plant resistance to the nematode, which may explain the low frequencies and low population densities found in the studied areas (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the endophyte F. oxysporum has the ability to induce a systemic resistance in banana plants against R. similis, reducing the penetration and the population density of this nematode (Felde et al, 2006;Paparu, Dubois, Coyne, & Vijoen, 2007;Vu, Hauschild, & Sikora, 2006). Other studies evidenced that the endophyte may exert an antagonistic activity against R. similis, which makes it a promising biological control agent (Athman et al, 2006;Mendoza & Sikora, 2009 (Ritzinger & Fancelli, 2006). It is likely that the interaction between Pratylenchus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aspergillus spp., Penicillium spp., and Chaetomium sp. are used in the industry for the production of secondary metabolites that exhibit antimicrobial and antifungal properties (Hanada et al, 2010;Li et al, 2011;Wang et al, 2012;Jouda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…strain Bonn-7 was isolated from cortical tissue of surface sterilized radish roots in Bonn, Germany (Xiaonin Yan, 2009, personal communication). These endorhiza colonizers were previously shown to have biocontrol activity against plantparasitic nematodes (Hallmann and Sikora 1994a, b;Pocasangre et al 2006;Dababat and Sikora 2007a, b, and c;Vu et al 2006;Mendoza and Sikora 2008).…”
Section: Endophytic Fungimentioning
confidence: 98%